DEKONSTRUKSI NILAI-NILAI KEBAIKAN CERPEN LELAKI YANG KEMBALI MENEMUI IBLIS KARYA FAWAIZUL UMAM - Herpin Nopiandi Khurosan (Universitas Sarjanawiyata Tamansiswa, 2020)
This study examines Fawaizul Umam’s Lelaki yang Kembali Menemui Iblis short story by applying Derrida's deconstruction theory. This study will try to answer whether the novel deconstructs binary opposition between goods and evils or establish the opposition in hierarchy. The result shows that there are pairs of oppositions created in the novel abort themselves and postpone the meaning structures they have.